Morphological variability of Consolida regalis seeds of south-eastern and central Europe. Issue 1 (2nd January 2017) - Rewicz, Agnieszka; Bomanowska, Anna; Magda, Joanna; Rewicz, Tomasz
Abstract : The aim of the paper was to analyse the morphological variability of Consolida regalis Gray (common name Forking Larkspur) seeds in populations derived from different geographic origins. A review of available literature showed scarcity of data on seed sizes and a complete lack of information describing the morphological variation of C. regalis seeds in the geographic gradient. Therefore, the main aim of the study was to analyse the morphological variability of C. regalis seeds from south-eastern and central Europe. Larkspur seeds, collected during expeditions spanning 2012–2014 from 29 sites located in Bulgaria, Romania, Moldova and Poland, were the study material. Four biometric traits were analysed, that is, the length, the width, the perimeter and the area of the seeds. The pictures of the surface structure and sculpture of the seeds were made using the scanning electron microscope (SEM). The results showed differences in biometric traits and the seed sculpture across the latitudinal transect. There was a trend observed of an increase in the length, the width, the perimeter and the area of the seeds towards the northern border of the geographic species range. Besides the geographic factor, the morphological variation of larkspur seeds was affected by environmental conditions (mainly temperature) in which plants grew and availability of habitat resources.